Effect of Synthetic Peptides Identified in the Bullfrog Skin on Inflammation and Oxidative Stress Control: An In Vitro Analysis - Silvânia Mól Pelinsari; Patricia da Silva Mattosinhos; Manoela Maciel dos Santos Dias; Rosinéa Aparecida de Paula; Romulo Dias Novaes; Emerson Ferreira Vilela; Giuseppe Valacchi; Reggiani Vilela Gonçalves (Molecules)
(1) Background: This study evaluated the potential of a synthetic peptide (SGHPGAMGPVGPR), identified in the bullfrog (Lithobates catesbeianus) skin, in regulating inflammation and oxidative stress using RAW 264.7 macrophages; (2) Methods: Molecular docking determined its optimal interaction with cyclooxygenase (COX-2) an enzyme related to the production of prostaglandins, which play a crucial essential role in the inflammatory response. The peptide was commercially synthesized company, and its antioxidant capacity was assessed using DPPH and FRAP assays. Cell viability, nitric oxide (NO) levels, catalase (CAT), superoxide dismutase (SOD) and glutathione s-transferase (GST) activity, interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) gene expression and cell production were additionally quantified. (3) Results: The peptide SGHPGAMGPVGPR, designated as P1, exhibited remarkable free radical scavenging capacity, antioxidant, and anti-inflammatory activities. No significant difference was observed in SOD and CAT activity in P1-treated macrophages, likely due to downregulation in the Nrf2/HO-1 pathway. Reduced GST activity was observed in these cells, which was potentially associated with TNF-α downregulation; (4) Conclusions: These findings suggest that P1 modulates the antioxidant response through pathways independent of classical antioxidant enzymes. Furthermore, decreased IL-6, COX2, and nuclear factor kappa B (NF-κB) expression was observed, indicating the involvement of a key pathway in the regulation of the OxInflammation process.